Колізійна доктрина вирішального виконання та принцип тісного зв'язку: континентальна традиція - Пшеничнюк, Д.В. (Часопис Київського університету права, 2009)
Статья содержит порядка применения коллизионного принципа тесной связи в странах ЕС. В статье показана связь между доктриной решающего исполнения и данным принципом. The article contains legal analysis of application of choice-of-law principles of the closest connection in EU’s states. This article shows interrelation between doctrine of characteristic performance and aforementioned principle.